2011
DOI: 10.1002/jez.b.21410
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of pleiotropy: epistatic interaction pattern supports a mechanistic model underlying variation in genotype–phenotype map

Abstract: The genotype-phenotype map consists of developmental and physiological mechanisms mapping genetic onto phenotypic variation. It determines the distribution of heritable phenotypic variance on which selection can act. Comparative studies of morphology as well as of gene regulatory networks show that the genotype-phenotype map itself evolves, yet little is known about the actual evolutionary mechanisms involved. The study of such mechanisms requires exploring the variation in genotype-phenotype maps at the popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 83 publications
1
60
0
1
Order By: Relevance
“…This is consistent with other rQTL studies (Pavlicev et al 2011b). APOE is the only locus to have a direct association with any of the traits (TC, LDL, ln TG, and HDL), which is already well established in the literature (Templeton et al 2005).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…This is consistent with other rQTL studies (Pavlicev et al 2011b). APOE is the only locus to have a direct association with any of the traits (TC, LDL, ln TG, and HDL), which is already well established in the literature (Templeton et al 2005).…”
Section: Resultssupporting
confidence: 92%
“…Sign epistasis occurs when the allelic effects change direction across genetic backgrounds. Pavlicev et al (2011b) found that rQTL have a higher proportion of sign epistatic interactions than non-rQTL. Sign epistasis sometimes involve compensatory mutations, which occur when the deleterious effect of a mutation at one locus is alleviated with a context dependency at another locus.…”
Section: Genetic Analysesmentioning
confidence: 95%
See 3 more Smart Citations